2016
DOI: 10.1007/s00170-016-9416-4
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling and experimental study on breakdown voltage (BV) in low speed wire electrical discharge machining (LS-WEDM) of Ti-6Al-4V

Abstract: In this study, the breakdown voltage behavior in low speed wire electrical discharge machining (LS-WEDM) of Ti-6Al-4V (TC4) in the deionized water is investigated. Firstly, the electric field distortion caused by impurity particles including TC4 or brass metal and bubbles is investigated. And then the breakdown voltage model of TC4 machined by LS-WEDM is established and the experimental verification result indicates that the model predicting results conforms to the actual processing and could be well follow ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Altug et al [25] applied different heat treatment processes to alter microstructure, mechanical and conductivity properties of Ti-6Al-4V and investigated effects of such heat treatment on machinability during WEDM process. Gong et al [18] observed reduced kerf width and inferior surface finish due to increased breakdown voltage during low-speed WEDM of Ti-6Al-4V in distilled water (as dielectric). Bigger-sized voids and intense surface cracks (deep and wide) were also obtained with an increase in breakdown voltage.…”
Section: State Of Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Altug et al [25] applied different heat treatment processes to alter microstructure, mechanical and conductivity properties of Ti-6Al-4V and investigated effects of such heat treatment on machinability during WEDM process. Gong et al [18] observed reduced kerf width and inferior surface finish due to increased breakdown voltage during low-speed WEDM of Ti-6Al-4V in distilled water (as dielectric). Bigger-sized voids and intense surface cracks (deep and wide) were also obtained with an increase in breakdown voltage.…”
Section: State Of Artmentioning
confidence: 99%
“…The WEDM parameters to be employed for multi-cut strategy are based on capabilities of the machine/set-up as well as past experience. According to Gong et al [18,19], poor thermal conductivity and plasticity of Ti-6Al-4V often cause wire rapture due to evolution of high machining temperature. Therefore, machining parameters of multi-cuts with wire offsets are modified to mitigate possibility of wire rapture and to ensure a favourable machining operation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, through technology research, this paper explores a high-precision and low-cost fabrication process of a MEMS S&A device: low-speed wire electrical discharge machining (EDM). As a flexible noncontact machining technology with strong advantages involving material selection [39], [40], the EDM process has unique advantages in micropart forming by wire electrode processing and nonmacro force processing [41]- [43]. By using the combined electrode fixture applied in EDM, multiple electrodes can work at the same time, which greatly improves the processing efficiency, and the machined parts have good consistency.…”
Section: Optimization Of the Setback Arming Device A Optimization Of The Processing Technologymentioning
confidence: 99%
“…Sarkar et al [34] studied the influence of pulse-on time, pulse-off time, peak current, wire tension, servo voltage, and dielectric flushing pressure on γ titanium aluminide alloy and stated that as the parameters were varied, the increase in cutting speed resulted in an increased surface roughness of the machined component. Gong et al [49] did an experimental study on the influence of break down voltage on kerf and surface roughness of a machined component. Authors stated that increase in the breakdown voltage magnitude would decrease kerf width and increase surface roughness.…”
Section: Effect Of Process Parametersmentioning
confidence: 99%